Identifying and delineating the type 2 diabetes population in the Netherlands using an all-payer claims database: characteristics, healthcare utilisation and expenditures - Dirk Ruwaard; Henk J G Bilo; Rose J Geurten; Arianne M J Elissen; Jeroen N Struijs; Chantal van Tilburg (BMJ Open)
Objectives We aimed to identify and delineate the Dutch type 2 diabetes population and the distribution of healthcare utilisation and expenditures across the health system from 2016 to 2018 using an all-payer claims database.Design Retrospective observational cohort study based on an all-payer claims database of the Dutch population.Setting The Netherlands.Participants The whole Dutch type 2 diabetes population (n=900 522 in 2018), determined based on bundled payment codes for integrated diabetes care and medication use indicating type 2 diabetes.Outcome measures Annual prevalence of type 2 diabetes, comorbidities and characteristics of the type 2 diabetes population, as well as the distribution of healthcare utilisation and expenditures were analysed descriptively.Results In 2018, 900 522 people (6.5% of adults) were identified as having type 2 diabetes. The most common comorbidity in the population was heart disease (12.1%). Additionally, 16.2% and 5.6% of patients received specialised care for microvascular and macrovascular diabetes-related complications, respectively. Most patients with type 2 diabetes received pharmaceutical care (99.1%), medical specialist care (97.0%) and general practitioner consultations (90.5%). In total, €8173 million, 9.4% of total healthcare expenditures, was reimbursed for the type 2 diabetes population. Medical specialist care accounted for the largest share of spending (38.1%), followed by district nursing (12.4%), and pharmaceutical care (11.5%).Conclusions All-payer claims databases can be used to delineate healthcare use: this insight can inform health policy and practice and, thereby, support better decisions to promote long-term sustainability of healthcare systems. The healthcare utilisation of the Dutch type 2 diabetes population is distributed across the health system and utilisation of medical specialist care is high. This is likely to be due to presence of concurrent morbidities and complications. Therefore, a shift from a disease-specific approach to a person-centred and integrated care approach could be beneficial in the treatment of type 2 diabetes.